Beach volleyball spike arm swing techniques of Olympics and world championships winners (1996-2019) reveal gender differences - Giatsis, G.; Tilp, M.; Hatzimanouil, D.; Dieckmann, C.; Stergiou, N. (International Journal of Sports Science & Coaching, 2022)
The spike attack is one of the most important skills in beach volleyball, and as an overarm movement, places significant load on the shoulder joint that could lead to increased risk of injury. An analysis of the different techniques used by elite athletes could provide important insights regarding the etiology of these injuries. This study aimed to assess the spike attack arm swing techniques of Olympics and World Championships (1996-2019) beach volleyball winners and to investigate possible gender differences. Twenty-five male and twenty female winners were assessed on video recordings from eighteen competitions. The different arm swing techniques in the cocking phase (Straight, Bow-and-arrow high, Bow-and-arrow low, Snap, and Circular) were classified by two experts. Intra-rater reliability of both experts ( = 1.000, P < .001 and = .969, P < .001 respectively) and inter-rater reliability ( = .969, P < .001), assessed by Cohen s Kappa, were almost perfect. There were significant gender differences in arm swing techniques (P < .001) with a large size effect (Cramer s V = .650). The most frequent technique for men was the Bow-and-arrow low (56%) followed by Circular (24%) and Bow-and-arrow high (20%), while for women were the Bow-and-arrow high (30%) and Snap (30%), followed by Bow-and-arrow low (25%) and Straight (15%). The results showed a great variation in arm swing techniques even among world class beach volleyball players as well as significant gender differences, and could allow us to develop interesting hypotheses regarding the mechanisms that could lead to shoulder overuse injuries.